Fish Community Assessment in Serayu Moveable Dam Post-Catastrophic Mortality - Wibowo, Dwi Nugroho; Rukayah, Siti; Ikegwu, Chukwudi Michael (Biosaintifika: Journal of Biology & Biology Education, 2025)
Catastrophic mortality occurred in the fish community at Serayu Movable Dam in 2022. The phenomenon was caused by severe water quality alteration due to sediment flushing from Panglima Besar Soedirman Dam. After the incident, the fish community in the reservoir has never been evaluated. This study aimed to assess the fish community status in the Serayu Movable Dam post-catastrophic mortality in 2022. The study was conducted using a survey method, and fish samples were collected three times at six sampling sites at an interval of two weeks. Fish identification was done using the identification key in the references. Various community and water quality parameters were measured. The data obtained were analyzed descriptively by comparing them with standards in the literature. A total of 27 species were identified with a richness index of 4.564, relative abundance of 0.037, diversity index of 2.111, evenness index of 0.693, and dominance index of 0.259. The data proved that the fish community in Serayu Movable Dam has recovered after two years of catastrophic mortality in 2022. It could be due to the characteristic of the riverine ecosystem that can revert due to the continuous replacement of water from various tributaries that flow into the Serayu River in the upstream part of the Serayu Movable Dam, as shown by good water quality. It can be concluded that high ichthyofauna diversity was observed in the Serayu Moveable Dam post-catastrophic mortality. The data are essential scientific bases for sediment flushing management at P.B. Soedirman Dam and management of freshwater fish community in Serayu Movable Dam.